Organizing Natural Tie-Dye Experience to Promote Executive Functions, Self-Regulation Skills Group: Attentional of Early Childhood - Sang-ngam , Suriyan; Puttasarin, Thipaugson (Journal of Buddhist Education and Research (JBER), 2025)
This research aimed: 1. To develop the attention behavior of early childhood before and after organizing the natural tie-dye experience. 2. To compare the attention behavior of early childhood before and after organizing the natural tie-dye experience. Research target group was 4-5 years old male and female early childhood in the second semester of the 2024 academic year, kindergarten 2 level, Thesaban 4 School (Amorn Sapianchai Uthit), Education Division, Chaiyaphum Municipality, consisted of 18 students, by purposive sampling. The research instruments consisted of organizing the natural tie-dye experience plan and the observation form of the attention behavior of early childhood. The researcher used the One-Group Pretest-Posttest Design. Data were analyzed using mean and standard deviation and t-test dependent. The results of the research found that organizing natural tie-dye experience to promote executive functions, self-regulation skills group: attentional of early childhood. Because the activity can stimulate early childhood to have continuous interest and focus more on learning. The natural tie-dyeing experience resulted in early childhood having higher attention behaviors before the experience, with statistical significance level .05.